2020
DOI: 10.1111/medu.14057
|View full text |Cite
|
Sign up to set email alerts
|

Self‐monitoring accuracy does not increase throughout undergraduate medical education

Abstract: Context Accurate self‐assessment of one's performace on a moment‐by‐moment basis (ie, accurate self‐monitoring) is vital for the self‐regulation of practising physicians and indeed for the effective regulation of self‐directed learning during medical education. However, little is currently known about the functioning of self‐monitoring and its co‐development with medical knowledge across medical education. This study is the first to simultaneously investigate a number of relevant aspects and measures that have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 35 publications
6
34
0
Order By: Relevance
“…With regard to the first research question, we found moderately high agreement between the external observations and team members' self-monitoring of their teams' teamwork. These findings are well in line with the literature on self-monitoring of one's individual performance on a moment-by-moment basis [31,35,39,40,48]. Our study extends this conception in two important ways.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to the first research question, we found moderately high agreement between the external observations and team members' self-monitoring of their teams' teamwork. These findings are well in line with the literature on self-monitoring of one's individual performance on a moment-by-moment basis [31,35,39,40,48]. Our study extends this conception in two important ways.…”
Section: Discussionsupporting
confidence: 91%
“…Although we cannot exclude that professional experience plays a role in the ability to self-monitor oneself, the literature on selfmonitoring suggests otherwise (e.g. [39,40]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such courses, students can watch and playback the teaching videos anytime, which reflects self-regulated learning in medical education. 34 Medical students in China have fewer experiences with live broadcast courses and blended learning. This suggests that instructors in formal medical education prefer traditional teaching methods, such as face-to-face lectures and experimental teaching.…”
Section: Discussionmentioning
confidence: 99%
“…via logbook can further increase the knowledge and motivation of students by reflecting their strengths and weaknesses regarding their clinical competence [ 33 , 34 ]. However, the appropriate form and content of self-reflection can be discussed controversely [ 35 ]. Therefore, self-reflection in contrext of learning risk-classification might be a relevant issue that should be considered in the further implementation of risk-oriented prevention in curricular dental education.…”
Section: Discussionmentioning
confidence: 99%